1999
DOI: 10.1021/jf990757d
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Accelerated Cumene Hydroperoxide Decomposition in Hexadecane and Trilaurin Emulsions

Abstract: Free radicals arising from lipid peroxides accelerate the oxidative deterioration of foods. To elucidate how lipid peroxides impact oxidative reactions in food emulsions, the stability of cumene hydroperoxide was studied in hexadecane or trilaurin emulsions stabilized by anionic (sodium dodecyl sulfate; SDS), nonionic (Tween 20), and cationic (dodecyltrimethylammonium bromide; DTAB) surfactants. Fe(2+) rapidly (within 10 min) decomposed between 10 and 31% of the cumene hydroperoxide in Tween 20- and DTAB-stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
2
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 14 publications
2
50
2
4
Order By: Relevance
“…However, it is important to note that the nature of the emulsifier used in emulsions may have a crucial effect on the action of prooxidants and antioxidants since the attractive or repulsive interactions between charged emulsion droplets and charged prooxidants and antioxidants greatly affect their location or concentration at the surface of dispersed lipids and hence their activity [39,40]. Thus, the more polar ferulic acid and caffeic acid showed higher activity than their corresponding phenethyl esters in oil-in-water emulsions stabilized by Triton X-100 [41], and the antioxidant activity of gallic acid and its methyl, ethyl, butyl and octyl esters showed markedly different trends in oil-in-water emulsions depending on whether an anionic emulsifier (SDS) or a nonionic emulsifier (Brij) was used [42].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to note that the nature of the emulsifier used in emulsions may have a crucial effect on the action of prooxidants and antioxidants since the attractive or repulsive interactions between charged emulsion droplets and charged prooxidants and antioxidants greatly affect their location or concentration at the surface of dispersed lipids and hence their activity [39,40]. Thus, the more polar ferulic acid and caffeic acid showed higher activity than their corresponding phenethyl esters in oil-in-water emulsions stabilized by Triton X-100 [41], and the antioxidant activity of gallic acid and its methyl, ethyl, butyl and octyl esters showed markedly different trends in oil-in-water emulsions depending on whether an anionic emulsifier (SDS) or a nonionic emulsifier (Brij) was used [42].…”
Section: Resultsmentioning
confidence: 99%
“…As such, surface-active LOOHs could concentrate at the oil-water interfaces of bulk oils, oil-in-water emulsions, or membrane systems. Indeed, several authors have reported the presence of LOOH at the emulsion droplet surface (Dimakou et al 2007;Mancuso et al 2000;Mei et al 1998a,b;Nuchi et al 2002;Yoshida & Niki 1992). In membrane systems, LOOHs float on the LDL surface (Ingold et al 1993).…”
Section: Self-assembly Of Lipid Hydroperoxides As a Trigger Of The Prmentioning
confidence: 99%
“…Cationic surface-active compounds have the potential to repel metals away from the oil-water interface, and thus retard oxidation as shown in O/W emulsions (Mancuso, McClements, & Decker, 2000;Mancuso et al, 1999;Mei et al, 1998). However, Denisov and Trunova reported that CTAB exerts a catalytic effect on the process of radical chain oxidation of hydrocarbons (Denisov & Afanas'ev, 2005;Trunova et al, 2007Trunova et al, , 2008.…”
Section: Effects Of Different Charged Surface-active Compounds On Thementioning
confidence: 99%